2019
DOI: 10.1049/iet-map.2018.5926
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐band band‐stop microstrip filter with controllable bands based on unequal split ring resonators

Abstract: In this study, a dual band band‐stop filter based on split ring resonators (SRR) over a ground plane with unequal rings is proposed and characterised. The proposed SRR design method, which is demonstrated here, ensures the control of the resonance frequencies and their respective bandwidths. The lengths and coupling regions of each ring are arbitrary, making possible the control of, not only the separation between the two generated resonances, but also the bandwidth ratio between the pass‐bands, or quality fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…It indicates that the proposed design is one of the only two designs which can produce the arbitrary number of DM stopbands simultaneously. The fourth row shows that it exhibits better stopband rejection level than all other designs except [1]. As seen from the fifth row, this engineered filter is one of those designs with the minimum DM return loss.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…It indicates that the proposed design is one of the only two designs which can produce the arbitrary number of DM stopbands simultaneously. The fourth row shows that it exhibits better stopband rejection level than all other designs except [1]. As seen from the fifth row, this engineered filter is one of those designs with the minimum DM return loss.…”
Section: Resultsmentioning
confidence: 85%
“…Bandstop filter (BSF) plays an important role in many radio frequency (RF) and microwave communication systems by protecting the receiver from jamming by high power signals. The development of modern communication systems with multi‐band services is attracting much attention for notch filters with multiple stopbands [1, 2]. For example, dual‐band BSFs are often used in high power amplifiers and mixers due to their ability to suppress the double sideband spectrum [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…The double resonances can be achieved by using unequal SRR, which leads to a more compact size. The second popular topology makes use of the first harmonics of a givenresonator's response as the second passband [8]- [13]. In this case, stepped impedance resonators (SIRs) are the most commonly used, where the impedances and the length ratio of the SIRs can be varied to obtain the desired operating frequency.…”
Section: Introductionmentioning
confidence: 99%
“…The resonant frequency of its component units is straightforward to adjust and can reach the terahertz frequency band. It has been widely researched and applied in many fields, such as filters [ 9 , 10 ], antennas [ 11 ], and energy harvesting [ 12 , 13 , 14 , 15 ]. It is shown that the antenna composed of the five split-ring resonators can realize multi-band communication [ 16 ].…”
Section: Introductionmentioning
confidence: 99%